Problem Based E-Book on Social and Natural Sciences Learning Subjects for Fifth Grade of Elementary Schools - Saputra, I Gede Putu Krisna Darma; Sukmana, Adrianus I Wayan Ilia Yuda (Jurnal Pedagogi dan Pembelajaran, 2024)
The limitations of teacher skills in developing innovative learning media affect student learning outcomes in the subject of social and natural sciences. This study was conducted with the aim of developing a product in the form of an e-book to improve student learning outcomes, as well as analyzing the validity, practicality, and effectiveness of the product developed. This study is a development research with the ADDIE model. This study involved expert lecturers and fifth grade elementary school students. The data collection method used questionnaires and tests. Then the data was analyzed descriptively quantitatively and statistically. Quantitative analysis techniques were used to test the design and validity stages of the products developed. In addition, this technique is used to process data obtained through questionnaires as descriptive percentages. Then statistical tests were carried out through the t-test which is useful for testing differences in the average value of the calculation between two correlated sample groups and independent samples. The results of the study showed that the overall validity results of the development of e-book teaching materials had a very good percentage and were suitable for use in the learning process. Based on this, it can be concluded that e-book media based on problem based learning are effectively applied to the subject of social and natural sciences in fifth grade elementary schools. This research has a positive impact on teachers, namely expanding teachers' knowledge in developing and utilizing learning media in the learning process so that teachers do not predominantly use lecture methods.